(untitled) (Journal of Economic Research & Business Administration, 2017)
This research is about the improvement of the mechanism of crisis management in the Republic of Kazakhstan. It has been worked hard in order to seek some helpful facts from amounts of data, documents, books and every possible resource useful. Every enterprise is vulnerable to crisis. The market has witnessed countless of examples that a small mistake or an unexpected weak changes, sometimes even a small incorrect business move from an enterprise under some certain circumstance might bring lethal result to the existing of the enterprise. And a lot of situations that can be threatening or could harm the enterprise by seriously interrupting business, significantly damaging image, and hampering the normal cash flow to trap the enterprise in an even worse dilemma of payment lack of monetary asset or bankruptcy. The proper mechanism of a crisis management enable the enterprises confront crisis effectively and efficiently. Nowadays Kazakhstan has become one of the countries with the richest natural resources, among which oil and gas industry takes the most important position compared with other industries and other resources. The oil and gas enterprises also formed a more flexible mechanism of crisis management system.